A study on factors that influence the small traders in making the successful business: a case on Pasar Tani Kekal in Jerantut, Pahang / Adhariana Mado - Mado, Adhariana (Bachelor of Business Administration (Hons) Marketing, 2013)
Permanent Farmer's Market is a development project to highlight the rapid changes and growth of Retail Farmers' Market. The participants of Permanent Farmers' Market will be placed under one roof, and they will carry out daily businesses. Pasar Tani Kekal Jerantut is one of the projects that being run by FAMA. This project was developed in 2006 and the operation started in 2007. A small trader is who doing the daily business in Pasar Tani Kekal (PTK) Jerantut, pahang. They run the business and sold wet and fresh products such as vegetables, fruits, poultry, water fresh fish, foods and drinks. However, there are small traders that successful in their business and also have those small traders not successful at PTK. By this situation, the small traders must know how to improve and make their business becomes successful. A study has been carried out to identify the main factor that influences the small traders in making the business successful at Pasar Tani Kekal in Jerantut, Pahang. Through some information, the research come up with four main factors which is strategic location, incentive programs, customer satisfaction, and hardworking of small traders. The respondents of for this study are small traders who doing business at Pasar Tani kekal Jerantut, Pahang. At the end of study, the researcher found that the strategic location is the most factors that influence the small traders in making business successful